Islam and international law : engaging self-centrism from a plurality of perspectives - Frick, Marie-Luisa, 1983- (Brill's Arab and Islamic law series., 2013)
Islam and International Law explores the multi-faceted relationship of Islam and international law. Current debates on Sharia, Islam and the "West" often suffer from prejudice and platitudes. The book seeks to engage such self-centrism by providing a plurality of perspectives, both in terms of interdisciplinary research and geographic backgrounds.